Competitive Advantage Analysis: Market Orientation and Entrepreneurial Orientation - Afif Maulana Ibrahim; Hapzi Ali (Siber International Journal of Sport Education, 2023)
Market orientation and entrepreneurial orientation are two important elements that can influence a company's competitive advantage. Market orientation focuses on the company's efforts to understand consumer needs and competition in the market, while entrepreneurial orientation emphasizes the company's ability to innovate, take risks, and be proactive in facing change. This article presents a literature review related to the influence of market orientation and entrepreneurial orientation on a company's competitive advantage. The results of this study are (1) market orientation has a significant influence on competitive advantage (2) entrepreneurial orientation has a significant influence on competitive advantage. (3) market orientation and entrepreneurial orientation have a simultaneous influence on competitive advantage.